1997
DOI: 10.1029/96jc02938
|View full text |Cite
|
Sign up to set email alerts
|

The origin of the North Pacific Intermediate Water

Abstract: Possible source regions of the North Pacific Intermediate Water (NPIW) were investigated with synoptic conductivity‐temperature‐depth surveys. In the Okhotsk Sea Kuril Basin a pycnostad (referred to as the Okhotsk Sea Mode Water (OSMW)) was found in the density range of 26.6–27 σθ. The pycnostad is not seen in the Western Subarctic Gyre (WSAG); thus it is an indicative water peculiar to the Okhotsk Sea. The maximum thickness is at 26.7–26.9 σθ (centered at 26.8 σθ) which coincides with the NPIW density range i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
263
1
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 341 publications
(282 citation statements)
references
References 20 publications
17
263
1
1
Order By: Relevance
“…Figure 13b indicates the NPIW pressure, ~ 400 dbars at the outer rim and 700 dbars in the center of the gyre. NPIW salinity is largely the same as Talley The low potential vorticity contour is a useful indicator for identifying the ventilation source of NPIW [Talley, 1988;Yasuda, 1997]. Yasuda [1997] found that OSMW is associated with low salinity and low potential vorticity.…”
Section: The Spatial Definition Area Of Npiw In the Subtropical Gyrementioning
confidence: 99%
See 3 more Smart Citations
“…Figure 13b indicates the NPIW pressure, ~ 400 dbars at the outer rim and 700 dbars in the center of the gyre. NPIW salinity is largely the same as Talley The low potential vorticity contour is a useful indicator for identifying the ventilation source of NPIW [Talley, 1988;Yasuda, 1997]. Yasuda [1997] found that OSMW is associated with low salinity and low potential vorticity.…”
Section: The Spatial Definition Area Of Npiw In the Subtropical Gyrementioning
confidence: 99%
“…NPIW salinity is largely the same as Talley The low potential vorticity contour is a useful indicator for identifying the ventilation source of NPIW [Talley, 1988;Yasuda, 1997]. Yasuda [1997] found that OSMW is associated with low salinity and low potential vorticity. Talley [1993] noted the unitbrm distribution of potential vorticity in the subtropical gyre on isopycnal surface c•0=26.8 and suggested that it has implications for NPIW ventilation.…”
Section: The Spatial Definition Area Of Npiw In the Subtropical Gyrementioning
confidence: 99%
See 2 more Smart Citations
“…Yasuda et al [1996] also showed that the salinity minimum can be created by isopycnal mixing of the Kuroshio/Oyashio waters with different structures of salinity and velocity and that vertical mixing shifts the newly formed salinity minimum toward depth for asymmetric salinity structure. Moreover, Yasuda [1997] concluded that NPIW is formed by the Oyashio transport maximum of 26.8rr 0 attributed to the Oyashio potential vorticity (f P-109/ O z) minimum from the mode water in the Sea of Okhotsk.…”
Section: Introductionmentioning
confidence: 99%